Metal-free, radical 1,6-conjugated addition of cyclic ethers with para-quinone methides (p-QMs) - More, Satish G.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2019)
An efficient method for metal-free C-C bond formation between p-quinone methides (p-QMs) and cyclic ethers via a radical pathway to afford substituted diarylmethanes and triarylmethanes or to effect the -alkylation of the cyclic ethers has been developed. Also, the synthesis of 3,3-disubstituted oxindoles with stereogenic quaternary carbon centers was successfully achieved under mild reaction conditions.

Metal-free regioselective cross dehydrogenative coupling of cyclic ethers and aryl carbonyls - Mane, Kishor D.; Mukherjee, Anagh; Vanka, Kumar; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2019)
A highly regioselective, efficient, and metal-free oxidative cross dehydrogenative coupling (CDC) of aryl carbonyls with cyclic ethers has been developed. This method offers easy access to substituted alpha-arylated cyclic ethers with a high functional group tolerance in good to excellent yields. The regioselectivity of this CDC reaction was confirmed by density functional theory (DFT)-based calculations.

Metal-free, acid-catalyzed 1,6-conjugate addition of NH-sulfoximines to para-quinone methides: accessing to diarylmethine imino sulfanone - More, Satish G.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
We have reported an efficient and metal-free method for the construction of alpha-diarylmethine imino sulfanone using acid-catalyzed 1,6-conjugate addition of sulfoximines on para-quinine methides (p-QMs). This method showed broad functional group tolerance and a wide range of substrate scope with good to excellent yield. The excellent protocol exhibits mild reaction conditions with high atom economy. The practicability of the present method was supported by a Gram-scale reaction.

Metal-free access to hindered N-alkyl sulfoximines via in-situ generated Aza-oxyallyl cations from functionalized alkyl bromide - More, Satish G.; Mane, Kishor D.; Suryavanshi, Gurunath (Asian Journal of Organic Chemistry, 2022)
Herein, we report a catalyst-free and mild synthetic method for the construction of hindered N-alkyl sulfoximines derivative. A wide range of hindered di-alkyl sulfoximines can be readily obtained from the reaction of alpha-bromo-hydroxamates with a variety of sulfoximines, including diaryl, aryl-alkyl, di-alkyl and heteroaryl sulfoximines.
Keywords: alpha-Bromo hydroxamates; Aza-oxyallyl cations; Di-alkyl sulfoximines; metal-free; Sulfoximines